Avaliação da eficiência e evolução de programas de pós-graduação em administração - Curcio, Isys Rodrigues (2016)
The postgraduate programs in business grew 40% between 2009 and 2014, therefore, an assessment is necessary to ensure the quality of these courses, identify regional asymmetries and strategic areas of knowledge. The purpose of this work is to use the Data Envelopment Analysis (DEA) and DEA Window to analyze the efficiency of the courses and their evolution between the years. According to the inputs and outputs adopted this dissertation contributes to the analysis of academic efficiency of the Business in postgraduate couses. The data used is from programs in Brazilian universities that have a PhD in Business, between the years 2004 to 2006, 2007 to 2009 and 2010 to 2012. In the period from 2004 to 2006 23.5% of the evaluated programs were effective. Between 2007 and 2009 39% of the programs were efficient and between 2010 to 2012 48.6% of programs reached maximum efficiency. To solve the DEA Window the period that stood out was from 2007 to 2009 with the largest number of programs with maximum efficiency on window average more than half of the courses have efficiency between 99% and 80%. Observed an increase in qualified publications and the number of theses. In contrast the number of permanent teachers decreased in almost all programs. also decreased the number of papers published in proceedings of technical-scientific events as these did not count as bibliographic productions.